A critical debate of the cultural and social effects of Valletta 2018 European Capital of Culture. Issue 1 (2nd January 2021) - Ebejer, John; Xuereb, Karsten; Avellino, Marie
ABSTRACT: The paper considers the hosting of the European Capital of Culture in Malta in 2018 in the light of the cultural and social effects on Malta's capital city, Valletta. Governance and impacts on Malta's tourism are also debated. The cultural sector was positively impacted with a varied and innovative programme. The expectations for Valletta 2018 was that the cultural scene in Malta would be taken to a much higher level. This did not happen largely because politicisation undermined the overall governance of the event. In the last two decades, ECoC was one of many projects and initiatives that brought about a process of Valletta's regeneration. There are concerns, however, that excessive commercialisation has reduced liveability.